Pengaruh Penggunaan Media Gambar Berseri terhadap Kemampuan Melengkapi Kalimat Rumpang (Jurnal Arjuna : Publikasi Ilmu Pendidikan, Bahasa dan Matematika, 2025)
This study aims to determine the effect of using sequential picture media on students' ability to complete cloze sentences among third-grade students at MI Al-Hikmah Masangan in the 2024/2025 academic year. The research method used in this study is a quasi-experimental design with a Non-Equivalent Control Group design. The research sample consisted of two classes: the experimental class, which received treatment using sequential picture media, and the control class, which did not receive any treatment. The instrument used in this study was a cloze test that had been tested for validity and reliability. The data obtained were analyzed using statistical tests. The population in this study comprised all third-grade students at MI Al-Hikmah Masangan in the 2024/2025 academic year, totaling 28 students. Based on the results of the analysis, a significant difference was found between the experimental and control classes. This is evidenced by the hypothesis test results, which showed a significance value of 0.021 < 0.05, leading to the rejection of H0 and the acceptance of H1. Therefore, it can be concluded that the use of sequential picture media has a significant effect on the ability of third-grade students at MI Al-Hikmah Masangan to complete cloze sentences.